Mutant GNAS detected in duodenal collections of secretin-stimulated pancreatic juice indicates the presence or emergence of pancreatic cysts. Issue 7 (2nd August 2012) - Kanda, Mitsuro; Knight, Spencer; Topazian, Mark; Syngal, Sapna; Farrell, James; Lee, Jeffrey; Kamel, Ihab; Lennon, Anne Marie; Borges, Michael; Young, Angela; Fujiwara, Sho; Seike, Junro; et al.
Abstract : Objective: Pancreatic cysts are commonly detected in patients undergoing pancreatic imaging. Better approaches are needed to characterise these lesions. In this study we evaluated the utility of detecting mutant DNA in secretin-stimulated pancreatic juice. Design: Secretin-stimulated pancreatic juice was collected from the duodenum of 291 subjects enrolled in Cancer of the Pancreas Screening trials at five US academic medical centres. The study population included subjects with a familial predisposition to pancreatic cancer who underwent pancreatic screening, and disease controls with normal pancreata, chronic pancreatitis, sporadic intraductal papillary mucinous neoplasm (IPMN) or other neoplasms. Somatic GNAS mutations (reported prevalence ∼66% of IPMNs) were measured using digital high-resolution melt-curve analysis and pyrosequencing. Results: GNAS mutations were detected in secretin-stimulated pancreatic juice samples of 50 of 78 familial and sporadic cases of IPMN(s) (64.1%), 15 of 33 (45.5%) with only diminutive cysts (<5 mm), but none of 57 disease controls. GNAS mutations were also detected in five of 123 screened subjects without a pancreatic cyst. Among 97 subjects who had serial pancreatic evaluations, GNAS mutations detected in baseline juice samples predicted subsequent emergence or increasing size of pancreatic cysts. Conclusion: Duodenal collections of secretin-stimulated pancreatic juice from patients with IPMNs have a similar prevalence of mutant GNAS to primary IPMNs, indicating that these samples are an excellent source of mutant DNA from the pancreas. The detection of GNAS mutations before an IPMN is visible suggests that analysis of pancreatic juice has the potential to help in the risk stratification and surveillance of patients undergoing pancreatic screening.